Estudo biomecânico da marcha de mulheres idosas ultrapassando obstáculos: efeito da atividade física - Mochida, Lígia Yumi (2008)
It is known that practicing regular exercises promotes several benefits to elderly individuals. However, no studies have assessed the effects of activity on obstacle negotiation with this population. Therefore, the objective of this research was to study the gait during obstacle negotiation of elderly women who were physically active and physically independent by means of the analysis of biomechanical variables to identify which adaptations are performed by each group when executing a more complex gait task. The sample was comprised of healthy elderly female subjects, in which ten were physically independent (PI) and the other ten were physically active (PA) for more than one year. Two biomechanical tools were utilized: kinematics and dynamometry. The volunteers performed two types of protocols at self-selected speed: unobstructed gait and obstructed gait. The obstacle was positioned in two different manners, one immediately before the force plate (P1) and the other just after the force plate (P2), so the authors could analyze the different phases of the lower limb (primary and secondary approach, and primary and secondary support) during the negotiation of an obstacle. Obstacle height was customized according to the volunteer s lower limb length, and the heights of 10, 20 and 30% were utilized from the verified measure. The order in which the volunteers performed the task was randomized, and each volunteer executed three valid trials to each experimental condition, with the total amount of 21 randomized trials. The analyzed variables were: stride length, toe and heel horizontal distances, toe and heel clearances, hip joint absolute angle, knee and ankle joints relative angles, first and second peak vertical forces, minimum vertical force, relative vertical impulse of the ground reaction force, and support time. The Friedman analysis of variance was applied to detect differences between the tasks, while the Mann-Whitney test was applied to indicate differences between the groups. Type-I Error was controlled with the significance level stipulated below 0.05 to both tests. The statistically significant results did not provide conclusions regarding the effect of physical activity on the gait during obstacle negotiation of elderly women. However, it was observed certain indications that physical activity promoted facilitation when negotiating the imposed perturbations. Perhaps, by analyzing other variables and higher obstacle heights, the differences between the groups may become more apparent.